Effect of Titanium Nitride (TiN) Nanoparticles on the Lubricity and Viscosity of Water-Based Drilling Fluid (Annual Transactions of the Nordic Rheology Society, 2024)
The effectiveness of the fluid's performance depends on the combined effect on its rheological, thermos-physical, chemical, and lubricity properties. In this paper, the effect of TiN nanoparticles on different properties of KCL-based water-based drilling fluid was evaluated. Results showed that the TiN nanoparticles among others increased the lubricity of the drilling fluid by 40% and reduced the filtrate loss by 9.8%. Moreover, the additive has shown an impact on the thermal, electrical conductivity, and rheological properties of the considered drilling fluid.